Farmers' Adaptation Strategy in Using Land During the Dry Season in Tappale Village, Bone Regency - Jermias, Emanuel Omedetho; Irmayanti; Idrus, Idham Irwansyah; Suhaeb, Firdaus W. (Formosa Journal of Sustainable Research, 2024)
The aim of this research is to determine the adaptive strategies of farming communities in dealing with the dry season in Tappale Village. Data collection techniques were carried out using observation, interviews and documentation methods. The results of field research show that: There are two adaptive strategies carried out by farming communities in facing economic difficulties caused by the cessation of agricultural activities when the dry season arrives, namely making savings, and looking for other work to increase income during the dry season